Enhanced solute transport and steady mechanical stimulation in a novel dynamic perifusion bioreactor increase the efficiency of the in vitro culture of ovarian cortical tissue strips - Fragomeni, Gionata; De Napoli, Luigi; De Gregorio, Vincenza; Genovese, Vincenzo; Barbato, Vincenza; Serratore, Giuseppe; Morrone, Giuseppe; Travaglione, Angela; Candela, Andrea; Gualtieri, Roberto; Talevi, Riccardo; Catapano, Gerardo (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction: We report the development and preliminary evaluation of a novel dynamic bioreactor to culture ovarian cortical tissue strips that leverages tissue response to enhanced oxygen transport, and adequate mechanical stimulation. In vitro multi-step ovarian tissue static culture followed by mature oocyte generation, fertilization and embryo transfer promises to use the reserve of dormant follicles. Unfortunately, static in vitro culture of ovarian tissue does not promote development of primordial to secondary follicles and sustain follicle viability and thereby limits the number of obtainable mature oocytes. Enhancing oxygen transport to, and exerting mechanical stimulation on, ovarian tissue in a dynamic bioreactor may more closely mimic the physiological microenvironment and thus promote follicle activation, development and viability. Materials and Methods: The most transport-effective dynamic bioreactor design was modified using 3D-models of medium and oxygen transport to maximize strip perifusion, and to apply tissue fluid dynamic shear stresses and direct compressive strains to elicit tissue response. Prototypes of the final bioreactor design were manufactured with materials of varying cytocompatibility, assessed by testing the effect of leachables on sperm motility. Effectiveness of bioreactor culture was characterized against static controls by culturing fresh bovine ovarian tissue strips for 7d at 4.8x10-5 m/s medium filtration flux in air at -15% maximal total compressive strain and by assessing follicle development, health and viability. Results and Conclusions: Culture in dynamic bioreactors promoted an effective oxygen transport to tissue and stimulated tissue with strains and fluid-dynamic shear stresses that, although non-uniform, significantly influenced tissue metabolism. Tissue strip culture in bioreactors made of cytocompatible polypropylene preserved follicle viability and promoted follicle development better than static culture, less so in bioreactors made of cytotoxic ABS-like resin.